Germany : Technical Note on the Future of German Mortgage-Backed Covered Bond (PF and Brief) and Securitization Markets. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
As part of the 2011 Financial Sector Assessment Program (FSAP) update for Germany, this Technical Note reviews recent developments of mortgage-covered bond (Pfandbrief) and mortgage securitization markets in Germany, and explores future prospects for each against the background of ongoing regulatory changes. It examines the characteristics of the two markets and their performance through the crisis, and analyzes some of the policy reactions that are currently tending to favor covered bonds over securitization. Some of the systemic vulnerabilities associated with covered bonds are also discussed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet